Pelatihan Pembuatan Bakpao Aneka Isi pada Remaja Putri di Kelurahan Mangasa, Tamalate, Kota Makassar: Training on Making Steamed Buns with Various Fillings for Young Women in Mangasa Subdistrict, Tamalate, Makassar City - SIMAREMARE, PERAWATI; Nuralfiah, Andi; Jusuf, Luthfiani; Anriyana, Nur Widya; Supriadi, Muh. Fadhil (Jurnal Edukasi dan Pengabdian kepada Masyarakat, 2025)
Many adolescents possess considerable potential; however, fear of failure, limited opportunities for self-expression, and inadequate access to training constrain their ability to produce culinary products with economic value. This community service program aims to enhance adolescents’ skills and self-confidence through training in the production of assorted-filled steamed buns (bakpao), a simple culinary product with notable market prospects. The training was delivered through lectures and hands-on practice. The instructional materials covered dough preparation techniques, filling variations, food hygiene, as well as strategies for packaging and marketing bakpao products. Evaluation results indicated significant improvements in participants’ knowledge, technical skills, and motovation in producing marketable bakpao. This initiative is expected to foster the development of culinary entrepreneurial among adolescents in Mangasa Subdistrict, Tamalate District, Makassar City.